Central plasticity and dysfunction elicited by aural deprivation in the critical period - Chen, Zhiji; Yuan, Wei (Frontiers in Neural Circuits, 2015)
The acoustic signal is crucial for animals to obtain information from the surrounding environment. Like other sensory modalities, the central auditory system undergoes adaptive changes (i.e., plasticity) during the developmental stage as well as other stages of life. Owing to its plasticity, auditory centers may be susceptible to various factors, such as medical intervention, variation in ambient acoustic signals and lesion of the peripheral hearing organ. There are critical periods during which auditory centers are easier to suffer from abnormal experiences. Particularly in the early postnatal development period, aural inputs are essential for functional maturity of auditory centers. An aural deprivation model, which can be achieved by attenuating or blocking the peripheral acoustic afferent input to the auditory center, is ideal for investigating plastic changes of auditory centers. Generally, auditory plasticity includes structural and functional changes, and some of which can be irreversible. Aural deprivation can distort tonotopic maps, disrupt the binaural integration, reorganize the neural network and change the synaptic transmission in the primary auditory cortex or at lower levels of the auditory system. The regulation of specific gene expression and the modified signal pathway may be the deep molecular mechanism of these plastic changes. By studying this model, researchers may explore the pathogenesis of hearing loss and reveal plastic changes of the auditory cortex, which will facilitate the therapeutic advancement in patients with severe hearing loss. After summarizing developmental features of auditory centers in auditory deprived animals and discussing changes of central auditory remodeling in hearing loss patients, we are aimed at stressing the significant of an early and well-designed auditory training program for the hearing rehabilitation.